2012
DOI: 10.1212/wnl.0b013e31826c1acd
|View full text |Cite
|
Sign up to set email alerts
|

Association of cognitive dysfunction with neurocirculatory abnormalities in early Parkinson disease

Abstract: Objective: Cognitive impairment and neurocirculatory abnormalities such as orthostatic hypotension (OH), supine hypertension (SH), and failure to decrease blood pressure at night (nondipping) occur relatively commonly in Parkinson disease (PD); however, whether cognitive dysfunction in early PD is related to neurocirculatory abnormalities has not been established. Cognitive dysfunction in PD is associated with white matter hyperintensities on MRI. We report results of an analysis of neuropsychological and hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 39 publications
3
122
2
3
Order By: Relevance
“…The same study also reported the presence of comorbid HTN in persons with PD resulted in decreased scores on tests of executive function (tests of executive function combined score PD + HTN-p = 0.041) compared to persons with PD + OH, PD + OH + HTN, or PD with no other vascular comorbidity [24]. The latter result is supported by Kim et al [25] who found a negative correlation between executive function scores (COWAT-grocery, p < 0.05; COWAT-phonemic, p < 0.05; Stroop Word Test, p < 0.05) and the standard deviation of systolic blood pressure (SBP) (normal cognition group = 13.0 ± 3.5, mild cognitive impairment group = 12.8 ± 2.9, dementia group = 18.8 ± 11.1). In contrast to the above studies which reported significant correlations between cardiovascular and/or cerebrovascular dysfunctions and cognitive dysfunctions, Idiaquez et al [23] reported that the presence of OH (p = 0.1) or postprandial hypotension (PPH) (p = 0.4) did not significantly affect cognitive or behavioral scores in persons with PD or Parkinson's disease dementia (PDD) (Frontal Assessment Battery (FAB) [35], Blessed Scale [36], Cornell scale for depression [37]).…”
Section: Executive Functionmentioning
confidence: 60%
See 4 more Smart Citations
“…The same study also reported the presence of comorbid HTN in persons with PD resulted in decreased scores on tests of executive function (tests of executive function combined score PD + HTN-p = 0.041) compared to persons with PD + OH, PD + OH + HTN, or PD with no other vascular comorbidity [24]. The latter result is supported by Kim et al [25] who found a negative correlation between executive function scores (COWAT-grocery, p < 0.05; COWAT-phonemic, p < 0.05; Stroop Word Test, p < 0.05) and the standard deviation of systolic blood pressure (SBP) (normal cognition group = 13.0 ± 3.5, mild cognitive impairment group = 12.8 ± 2.9, dementia group = 18.8 ± 11.1). In contrast to the above studies which reported significant correlations between cardiovascular and/or cerebrovascular dysfunctions and cognitive dysfunctions, Idiaquez et al [23] reported that the presence of OH (p = 0.1) or postprandial hypotension (PPH) (p = 0.4) did not significantly affect cognitive or behavioral scores in persons with PD or Parkinson's disease dementia (PDD) (Frontal Assessment Battery (FAB) [35], Blessed Scale [36], Cornell scale for depression [37]).…”
Section: Executive Functionmentioning
confidence: 60%
“…Four out of seven studies included for analysis stated a significant p-value of less than 0.05 [23] [25] [27] [29]. In three of the seven studies, a p-value for significance was not explicitly stated, however, all p-values reported as significant by the authors were less than 0.05 [22] [24] [28].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations